Immobilization of Ionic Liquid on a Covalent Organic Framework for Effectively Catalyzing Cycloaddition of CO2 to Epoxides - Yan, Qianqian; Liang, Hao; Wang, Shenglin; Hu, Hui; Su, Xiaofang; Xiao, Songtao; Xu, Huanjun; Jing, Xuechao; Lu, Fei; Gao, Yanan (Molecules (Basel, Switzerland), 2022)
Transforming CO2 into value-added chemicals has been an important subject in recent years. The development of a novel heterogeneous catalyst for highly effective CO2 conversion still remains a great challenge. As an emerging class of porous organic polymers, covalent organic frameworks (COFs) have exhibited superior potential as catalysts for various chemical reactions, due to their unique structure and properties. In this study, a layered two-dimensional (2D) COF, IM4F-Py-COF, was prepared through a three-component condensation reaction. Benzimidazole moiety, as an ionic liquid precursor, was integrated onto the skeleton of the COF using a benzimidazole-containing building unit. Ionization of the benzimidazole framework was then achieved through quaternization with 1-bromobutane to produce an ionic liquid-immobilized COF, i.e., BMIM4F-Py-COF. The resulting ionic COF shows excellent catalytic activity in promoting the chemical fixation of CO2 via reaction with epoxides under solvent-free and co-catalyst-free conditions. High porosity, the one-dimensional (1D) open-channel structure of the COF and the high catalytic activity of ionic liquid may contribute to the excellent catalytic performance. Moreover, the COF catalyst could be reused at least five times without significant loss of its catalytic activity.